Effectiveness of a Home-Based Postal and Telephone Physical Activity and Nutrition Pilot Program for Seniors. (10th August 2010) - Lee, Andy H.; Jancey, Jonine; Howat, Peter; Burke, Linda; Kerr, Deborah A.; Shilton, Trevor
Abstract : Objective . To evaluate the effectiveness of a 12-week home-based postal and telephone physical activity and nutrition pilot program for seniors. Methods . The program was delivered by mailed material and telephone calls. The main intervention consisted of a booklet tailored for seniors containing information on dietary guidelines, recommended physical activity levels, and goal setting. Dietary and walking activity outcomes were collected via a self-administered postal questionnaire pre- and postintervention and analysed using linear mixed regressions. Of the 270 seniors recruited, half were randomly selected for the program while others served as the control group. Results . The program elicited favourable responses. Postintervention walking for exercise/recreation showed an average gain of 27 minutes per week for the participants in contrast to an average drop of 5 minutes for the controls (P < .01 ). Little change was evident in errand walking for both groups. The intervention group (n = 114 ) demonstrated a significant increase in fibre intake (P < .01 ) but no reduction in fat intake (P > .05 ) compared to controls (n = 134 ). Conclusions . The participants became more aware of their health and wellbeing after the pilot program, which was successful in increasing time spent walking for recreation and improving fibre intake.